1981
DOI: 10.1007/bf00484578
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the major urinary proteins in mouse liver: A biochemical genetic study

Abstract: By labeling liver protein in vivo with [3H] leucine, the relative biosynthetic rate has been measured for the major urinary proteins (MUPs), three closely related, androgen-regulated proteins that are synthesized in mouse liver, secreted into the bloodstream, and excreted into the urine. In livers from females of strain C57BL/6J, total MUP synthesis represents about 0.6-0.9% of the total protein synthesis; in males and testosterone-treated females of the same strain, synthesis increases to about 3.5-4.0% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Proteins before or after IP were electrophoresed in polyacrylamide (5%-12%), transferred to HyBond ECL nitrocellulose (Amersham), and probed with antibody against CBP80, eIF4E (Santa Cruz), eIF4GI (Bushell et al 2000), eIF2␣ (Santa Cruz), eIF3 (Etchison et al 1982), PABP1 (Gorlach et al 1994), PABP2 (Krause et al 1994), 4E-BP1 (Gingras et al 1998), one of the Upf proteins (Ishigaki et al 2001), HA (Roche), Penta-His (QIAGEN), calnexin (StressGen), or MUP (Berger and Szoka 1981). Reactivity to each antibody was detected using horseradish peroxidaseconjugated donkey ␣-rabbit (Amersham), sheep ␣-mouse (Amersham), donkey ␣-goat (Amersham), or rabbit ␣-rat antibody (Sigma).…”
Section: Western Blottingmentioning
confidence: 99%
“…Proteins before or after IP were electrophoresed in polyacrylamide (5%-12%), transferred to HyBond ECL nitrocellulose (Amersham), and probed with antibody against CBP80, eIF4E (Santa Cruz), eIF4GI (Bushell et al 2000), eIF2␣ (Santa Cruz), eIF3 (Etchison et al 1982), PABP1 (Gorlach et al 1994), PABP2 (Krause et al 1994), 4E-BP1 (Gingras et al 1998), one of the Upf proteins (Ishigaki et al 2001), HA (Roche), Penta-His (QIAGEN), calnexin (StressGen), or MUP (Berger and Szoka 1981). Reactivity to each antibody was detected using horseradish peroxidaseconjugated donkey ␣-rabbit (Amersham), sheep ␣-mouse (Amersham), donkey ␣-goat (Amersham), or rabbit ␣-rat antibody (Sigma).…”
Section: Western Blottingmentioning
confidence: 99%
“…Age-and sex-related expression of liver proteins is subject to a variety of control mechanisms, including transcriptional and post-translational regulation (17,18). In the studies reported here, we wished to determine whether C4 expression is subject to genetic regulation at the level of protein synthesis.…”
mentioning
confidence: 99%
“…The liver secretes a variety of proteins, including insulin likegrowth factor-1 (IGF-1), insulin-like growth factor-binding proteins, fibroblast growth factor-21 (FGF-21) and major urinary proteins (MUPs) (2)(3)(4)(5)(6). Insulin-like growth factor-binding proteins and FGF-21 have been well documented to regulate multiple aspects of glucose and lipid metabolism in animals (2,3,7).…”
mentioning
confidence: 99%
“…Comparative genomic analyses identify nine MUP genes in rats and a single MUP gene in other mammals (10). MUP1 (ϳ18 kDa in mass) is abundantly expressed in hepatocytes (3.5-4% of total protein synthesis) and secreted into the bloodstream (6,12). MUP1 binds via its central hydrophobic pocket to lipophilic molecules, including volatile pheromones (small odorant molecules) (5,13).…”
mentioning
confidence: 99%